Learning About Work Tasks to Inform Intelligent Assistant Design - Trippas, Johanne R.; Spina, Damiano; Scholer, Falk; Awadallah, Ahmed; Bailey, Peter; Bennett, Paul; White, Ryen W.; Liono, Jonathan; Ren, Yongli; Salim, Flora D.; Sanderson, Mark (The Fourth ACM SIGIR Conference on Human Information Interaction and Retrieval (CHIIR 2019), 2019)
Intelligent assistants can serve many purposes, including entertainment (e.g. playing music), home automation, and task management (e.g. timers, reminders). The role of these assistants is evolving to also support people engaged in work tasks, in workplaces and beyond. To design truly useful intelligent assistants for work, it is important to better understand the work tasks that people are performing. Based on a survey of 401 respondents' daily tasks and activities in a work setting, we present a classification of work-related tasks, and analyze their key characteristics, including the frequency of their self-reported tasks, the environment in which they undertake the tasks, and which, if any, electronic devices are used. We also investigate the cyber, physical, and social aspects of tasks. Finally, we reflect on how intelligent assistants could influence and help people in a work environment to complete their tasks, and synthesize our findings to provide insight on the future of intelligent assistants in support of amplifying personal productivity.